How did Bangladesh Quintuple Rice Output and Quadruple Its Yield in Seven Decades? An Analysis of Seasonal Land-Use Changes and Implications for Economic Development - Mohammad Alauddin; Clement A. Tisdell; Abdur Rashid Sarker; Zeenatul Islam (Journal of Agriculture and Environment for International Development)
Despite the critical importance of rice production in Bangladesh, linking productivity trends and the annual and seasonal dimensions of land use in rice farming remains largely unexplored This study addresses this gap by employing seventy-four years of national data, up to 2020, to examine the significance and implications of rice farming and land use changes for Bangladesh’s economic development. Increased irrigated rice areas contributed to total (wet and dry season combined) rice output and yield. We found evidence of different time trajectories of the seasonal diffusion of high-yielding variety (HYV) rice; and a varying pace of production and yield growth of dry and wet season HYV rice. The paces of growth of total and dry season HYV rice outputs and yields have been tapering off more recently, in contrast to those for the wet season. Seasonal land-use changes over time have resulted in more even agricultural employment and the availability of foodgrains throughout the year. Results show that agriculture’s share in total employment declined from < 70% to ≈38% and the declining trend was faster during 2000-2006. The percentage shares of the industry and service sectors increased to 21.32% and 40.38%, respectively, in 2019. However, the quadrupling of rice yield and rising labor productivity have placed Bangladesh on a higher economic growth path. Our findings suggest that despite eco-environmental challenges in intensification methods, agriculture, including rice production, will continue to be an essential part of Bangladesh’s economy.